Peningkatan Kompetensi Mahasiswa Keperawatan Melalui Strategi Pembelajaran Berbasis Virtual Reality - Ike Puspitaningrum; Rr. Sri Endang Pujiastuti; Kurniati Puji Lestari (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2019)
Nursing higher education has new challenges to prepare nursing students as agents of change in the era of the industrial revolution 4.0. Nursing students today are millennial and Z generation with unique needs and ways of learning. Students more interested in digital-based learning media. Digital-based learning methods were an urgent need to be developed to provide solutions to the learning needs of the millennial generation. The systematic review aimed to discuss the use of VR technology for educating the nursing student. The databases searched included: PubMed, Springerlink and Proquest from the years 2015 to 2019 with the keywords virtual reality, virtual simulation, simulation technology, immersive learning. The inclusion criteria included: articles published in the English language, student respondents and randomized controlled trial (RCT) research methods. The results of article was identified and reviewed by 3 researchers. Researchers approved 158 titles of article that match the keywords without duplicates and 5 articles that match the inclusion criteria. Four articles discuss the students' competencies when using virtual simulations compared with the manikin simulated. The results showed an increase in psychomotor skills, communication, and knowledge. Self-confidence increases, learning satisfaction and anxiety levels decrease. Two articles discuss the analysis of the unit cost, which states that the virtual simulation has cost utility ratio more profitable compared with the Manikin simulations. The results of the systematic review showed that virtual reality was relevant method as a learning strategy to enhance students’ competencies and have more profitable costs compared to conventional methods.